Rockface surficial temperatures at the Cântaro Gordo, northern slope, Serra da Estrela, Portugal, 1999-2001 - Gonçalo Vieira; Carla Mora (PANGAEA, 2019)
The dataset includes rock temperature data from the south and north slopes of the Cântaro Gordo, a granitic ridge rising to 1,875 m asl at the Serra da Estrela, Central-North Portugal ( 40°20 extquotesingle9"N, 7°35 extquotesingle52.75"W). The temperatures were measured at 1, 5, 10 and 17 cm depth at 2-hour intervals, from december 1999 to april 2001. The loggers were installed at vertical granite rockfaces at 1,860 m asl (north face) and 1,870 m asl (south face) without vegetation other than lichens. The data loggers were single channel Tiny Talk II loggers (Gemini), with 8-bit and 2k EEPROM memmory, with sensors being NTC100 thermistors. The data results from the project PRAXIS/P/CTE/11153/98 funded by the Fundação para a Ciência e a Tecnologia and are made available in the framework of the Núcleo de ciência e educação em território, clima e alterações climáticas of the Aspiring Geopark Estrela.